Blockade of periostin-dependent migration and adhesion by curcumol via inhibition of nuclear factor kappa B signaling in hepatic stellate cells. (July 2020) - Jia, Yan; Gao, Liyuan; Yang, Xiang; Zhang, Feng; Chen, Anping; Wang, Shijun; Shao, Jiangjuan; Tan, Shanzhong; Zheng, Shizhong
Graphical abstract: Abstract: Objectives: Curcumol, a guaiane-type sesquiterpenoid hemiketal extracted from the herb Rhizoma Curcumae, exhibits multiple-pharmacological activities. We previously reported that curcumol ameliorated hepatic fibrosis by inhibiting hepatic stellate cell (HSC) activation. In this study, we aimed to investigate the effect of curcumol on HSC migration and adhesion, and reveal its regulation mechanisms. Materials and methods: Cellular viability was determined by Cell Counting Kit-8. Cell migration was detected by boyden chamber and cell scratch experiment. Recombinant human periostin (rh POSTN) and adeno-associated viral (AAV)-GFP-periostin were used to achieve POSTN overexpression in vitro and in vivo, respectively. Nuclear factor kappa B (NF-κB)-p65 overexpression was achieved by using plasmid. ELISA was conducted to detect POSTN level. Immunohistochemistry, qRT-PCR, Western blotting, and immunofluorescence were performed to assess associated factor expression. Results: Curcumol suppressed HSC migration and adhesion, and reduced the secretion and expression of POSTN. By gain of function POSTN in HSCs, using rh POSTN, we found that the inhibition of HSC migration and adhesion by curcumol depended on the decrease of POSTN. Besides, curcumol protection against chronic CCl4 -caused hepatic fibrosis could be impaired by POSTN overexpression. Moreover, we showed that curcumol repressed NF-κB signaling and the production of pro-inflammatory factor. Importantly, curcumol down-regulation of POSTN was rescued by knock-in of NF-κB, as well as the inhibition of HSC migration and adhesion. Conclusion: These findings reveal the molecular mechanism of curcumol-reduced HSC migration and adhesion, by which points to the possibility of using curcumol based on NF-κB dependent POSTN for the treatment of fibrogenesis.